Clinical effectiveness of a child-specific dynamic stretching programme, compared to usual care, for ambulant children with spastic cerebral palsy (SPELL trial): a parallel group randomized controlled trial - Tim Theologis; Daniel C. Perry; Ines Rombach; David J. Keene; Ioana R. Marian; Morag Andrew; Catherine Barry; Loretta Davis; Gregory Firth; Heidi Fletcher; Beth Fordham; Vivi Gregory Osborne; et al. (Bone & Joint Open)
Aims: Dynamic muscle stretching exercises are one of the interventions frequently prescribed by physiotherapists for children with cerebral palsy (CP). However, there is wide variability in the exercise regimes used and limited evidence of their effectiveness. The SPELL trial will assess the clinical effectiveness of an individually tailored dynamic stretching programme, compared to usual care for ambulant children with spastic CP. Methods: We are conducting a multicentre, two-arm, parallel group, superiority randomized controlled trial. We will recruit children aged four to 11 years with a diagnosis of spastic CP (bilateral or unilateral) and Gross Motor Function Classification System (GMFCS) levels I to III who are able to comply with assessment procedures and exercise programme with or without support. Participants will be recruited from at least 12 UK NHS Trust physiotherapy and related services. Participants (n = 334) will be randomized (centralized computer-generated one:one allocation ratio) to either: 1) a dynamic stretching exercise programme, with six one-to-one physiotherapy sessions over 16 weeks; or 2) usual NHS care, with a single physiotherapy session and an assessment, and advice regarding self-management and exercise. Conclusion: The primary outcome is functional mobility measured using the child-/parent-reported Gait Outcomes Assessment List (GOAL) at six months. Secondary outcomes are: joint range of motion (Cerebral Palsy Integrated Pathway protocol) and motor function (timed up and go test) at six months; functional mobility (GOAL) at 12 months; independence (GOAL subdomain A); balance (GOAL subdomain A, B, D); pain and discomfort (GOAL subdomain C); health-related quality of life (youth version of the EuroQol five-dimension questionnaire (EQ-5D-Y)); educational attendance; exercise adherence; and additional physiotherapy treatment at six and 12 months. The primary analysis will be intention to treat. Cite this article: Bone Jt Open 2025;6(5):506–516.